Effect of Annealing Temperature and Time Over the Microstructural, Mechanical and Electrical Properties of Deformed Al Wires (A6) - Lin CHEN; Meigui OU; Yilong LIANG; Yu LIANG (Medžiagotyra)
Al wires with different deformation were obtained by cold-drawing and annealing treatment. The microstructure, mechanical, and electrical properties of the wires annealed at different temperatures and times were studied using SEM, universal testing machine, and DC resistance tester. The results indicate that as the annealing temperature and time increase, the UTS of Al decreases, while the EL and EC increase simultaneously. During the annealing procedure, recrystallization is observed to begin at 300 ℃ and complete at 350 ℃. Compared with the beginning of recrystallization, the recrystallized grain diameter increases from 11.34 μm to 20.59 μm, while the UTS decreases by 24.1 %, the EL increases by 74 %, and the EC increases by 3 %. When annealed at 315 ℃ for 1h, the recrystallization begins in the samples with 90 % deformation, and completes when the annealing time is increased to 4.5 h, the grain diameter increases from 7.67 μm to 20.71 μm; though the tensile decreases by 24.3 %, the EL and EC increase by 97.5 % and 2.8 %, respectively.